The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ps.6009
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR‐based metabonomic evaluation of the pesticides camptothecin and matrine against larvae of Spodoptera litura

Abstract: BACKGROUND: Camptothecin (CPT) and matrine (MAT) have potential as botanical pesticides against several pest species. However, the mechanisms of metabolic and physiological changes in pests induced by CPT and MAT are unknown. In this study, a toxicological test, an NMR-based metabolomic study, an enzymatic test, and an RT quantitative PCR (RT-qPCR) experiment were all conducted to examine the effect of CPT and MAT on Spodoptera litura. RESULTS: CPT (0.5-1%) exerted high toxicity against larvae of S. litura and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Furthermore, compared with the control group, substances related to glucose metabolism in the epidermis of H. armigera were down-regulated after ZQ-8 treatment (Figure 6), indicating that ZQ-8 reduced the glycolytic pathway. This was consistent with the fact that camptothecin inhibited the growth of Spodoptera litura larvae through decreased glycolysis and increased TCA cycle reported by Deng et al [24].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, compared with the control group, substances related to glucose metabolism in the epidermis of H. armigera were down-regulated after ZQ-8 treatment (Figure 6), indicating that ZQ-8 reduced the glycolytic pathway. This was consistent with the fact that camptothecin inhibited the growth of Spodoptera litura larvae through decreased glycolysis and increased TCA cycle reported by Deng et al [24].…”
Section: Discussionsupporting
confidence: 92%
“…found that 0.5% camptothecin strongly impacted fumarate and several energy‐related metabolites in Spodoptera litura (Dai et al. , 2021). Tavsan et al.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicological test was performed based on a previous protocol with some modifications (Dai et al ., 2020). In brief, a total of 180 3rd instar larvae were divided into 12 groups (15 larvae of each group).…”
Section: Methodsmentioning
confidence: 99%